Research on the Image of Yanqing in Mainstream Media Coverage of the Winter Olympics - Yang, Jie; Du, Bingxin (International Journal of Social Sciences and Public Administration, 2024)
The successful hosting of large-scale sports events can assist in the construction and dissemination of urban media image, and enhance urban competitiveness. This article mainly takes news reports on Yanqing from three mainstream media outlets, namely People’s Daily, Beijing Daily, and Beijing Evening News, during the Winter Olympics as research samples. Using methods such as content analysis, the article analyzes Yanqing’s urban media image from multiple perspectives by analyzing the emotional color, coverage density, themes, and keyword frequency of news reports. It presents a good media image of Yanqing built at different levels such as government, environment, culture, and society during the Winter Olympics.